Modeling of Overpressure Generation–Evolution of the Paleogene Source Rock and Implications for the Linnan Sag, Eastern China - Li, Chao; Zhang, Likuan; Luo, Xiaorong; Wang, Bing; Lei, Yuhong; Cheng, Ming; Luo, Hongmei; Wang, Changjiang; Yu, Lan (Frontiers in Earth Science, 2022)
Subsurface pore pressure affects the direction of hydrocarbon migration, determines the distribution of the hydrocarbon reservoir, and provides scientific reference for drilling planning. Overpressures are widespread in the Paleogene Shahejie Formation in the Linnan Sag, which is closely related to distribution of oil reservoir. However, the overpressure generation mechanisms are undefined, let alone the relationship between the evolution of paleo-overpressure and hydrocarbon migration in the Linnan Sag, which brings great challenges for understanding of oil accumulation and future oil exploration. Basin modeling was carried out to solve the issue of quantitatively evaluation of overpressure mechanisms, and to restore the overpressure evolution of the Paleogene source rocks. The implications for the pore pressure prediction and oil migration in Linnan Sag were further discussed. The modeling results show that the disequilibrium compaction of mudstones is dominated overpressure mechanism of source rocks in the Linnan Sag, which accounts for approximately 90% of the measured overpressure in the region. The remainder part of overpressure was generated by hydrocarbon generation, however the effects of hydrocarbon generation on overpressure evolution was limited in the intervals deeper than 4000m. The significance of the overpressure mechanism is that the porosity-depended method will give a satisfactory pressure prediction result in current exploration depth range (3800-4300m). The overpressure evolution of the source rock undergone a cycle of “accumulation-dissipation-reaccumulation”, which correspond to the age of 45.5-24.0Ma (Es3-Ed period), 24.6-14.0 Ma (Ed period) and 14.0-0Ma (Ng-Qp period). The oil potential of the Es3l shows a good inheritance with the overpressure in the source rock, indicated overpressure increased the driving force for oil migration. The oil released from the source rock has a trend to migration from the central of the sag to the uplift belt, which is also indicated by the physical properties of crude oil. The knowledge of the generation and evolution of overpressure has great significance for further exploration in the Linnan Sag and other extensional basins.